TINJAUAN KOREKSI FISKAL LABA RUGI KOMERSIAL PADA PT.SWAKITA INDONESIA - Yenti S, Dame Febri; Sitorus, Frangky Yosua; Lumbantoruan, Rutman L.Toruan (Fakultas Ekonomi Universitas Kristen Indonesia, 2017)
Fiscal correction performed by the taxpayer because there are differences in the calculation of the profit according to the accounting in particular (commercial) with the profit according to the tax (fiscal). Knowing PT.Swakita Indonesia in the income statement in accordance with the tax laws of Corporate Income Tax Act No. 36 of 2008 Article 9 paragraph 1 letter (b) that